Molecular Characterization and Functional Analysis of the Hb-hsp90-1 Gene in Relation to Temperature Changes in Heterorhabditis bacteriophora - Fanelli, Elena; Troccoli, Alberto; Tarasco, Eustachio; De Luca, Francesca (Frontiers in Physiology, 2021)
Understanding how entomopathogenic nematodes respond to temperature changes and have adapted to the local environment is crucial to improve their potential as biocontrol agents. In order to improve understanding of Heterorhabditis bacteriophora’spotential adaptability to future climate changes, full-length cDNA and the corresponding gene of heat shock protein 90 (Hsp90) were isolated and fully characterized. The reproductive potential of the Apulian strain of H. bacteriophora increased when the temperature rose from 23°C to 30°C, but no reproduction was found at 12°C. Expression analyses revealed that Hb-hsp90-1 was differentially expressed in Infective Juveniles (IJs) and adults (hermaphrodites, females and males). Up-regulation of Hb-hsp90-1 was higher during the recovery process in Galleria mellonella larvae than adults, thus confirming the protective role of Hb-hsp90-1 in coping with the host environment. Silencing of Hb-hsp90-1 resulted in a significant reduction (76%) in the expression level. Silenced IJs took longer than untreated nematodes to infect G. mellonella, showing that Hb-hsp90-1 is also involved in chemosensation. Furthermore, the number of adults and IJs recovered from G. mellonella infected with silenced nematodes and incubated at 30°C was higher than that obtained from G. mellonella infected with untreated nematodes. These data confirm the crucial role of Hb-hsp90-1allowing acclimation to increased temperatures and modulation of the host-seeking strategy.